THE INFLUENCE OF INFORMATION QUALITY, PROMOTION, AND SERVICESCAPE ON REVISIT INTENTION MEDIATED BY VISITOR SATISFACTION DURING THE NEW NORMAL ERA OF COVID-19 IN DUNIA FANTASI JAKARTA - Regina Dewi Hanifah; Rilla Rianty; Sundring Pantja Djati; Jakaria Jakaria; Anak Agung Gde Agung (Bajang Institute, 2022)
The Covid-19 virus has resulted in a number of government regulations and policies. It also has an impact on the Dunia Fantasi Jakarta, one of the most popular tourist attractions in Indonesia's capital city, which must learn to adapt to various health protocols imposed by the government. The purpose of this study is to determine how the quality of information, promotion, and servicescape affect revisit intention, with visitor satisfaction acting as a moderator. This research using testing hypothesis method was conducted on 200 respondents who used the website of Taman Impian Jaya Ancol. The data was analyzed statistically using Smart PLS tools. The findings revealed that the variable quality of information had no positive effect on customer satisfaction or intent to return. Promotion and servicescape, on the other hand, had a positive effect on customer satisfaction and revisit intention, and customer satisfaction had a positive effect on revisit intention. Then the visitors' perceptions of promotion and servicescape mediated by visitor satisfaction obtained a positive and significant effect on revisit intention. In contrast, the quality of information mediated by customer satisfaction did not significantly affect the revisit intention variable.